Технико-экономический анализ способов поддержания температуры в тепловых аккумуляторах - Сиворакша, В. Е.; Марков, В. Л. (НТУ "ХПИ", 2008)
Methods of technical and economical analysis of ways of keeping the temperature in heat storage units are suggested, the methods allowing estimating the influence of components of reduced annual expenses for heat protection of units and to determine an optimal thickness of a thermal insulating layer with a fixed value of the coefficient of thermal conductivity.
Keywords: системы теплотехнические; насос тепловой; теплопотери; термоэлектронагреватели; установка солнечная; ветроагрегаты